Encyclopedia of polymer and rubber additives - Wypych, George (ChemTec Publishing, 2024)
"The Encyclopedia of Polymer and Rubber Additives is an invaluable reference for chemists, engineers, and other professionals. It provides a complete set of tables, classifications, and information related to a wide variety of commercially used additives for polymers and rubbers. The book details the characteristics of hundreds of additives that can improve performance in terms of physical properties, stability, and storage life; provide colorants; reduce cost; improve processing or assembly; extend shelf life; enhance the purity and minimize environmental impact."--